Kant's theory of freedom - Allison, Henry (Cambridge Cambridge University Press, 1990)
In his new book the eminent Kant scholar Henry Allison provides an innovative and comprehensive interpretation of Kant's concept of freedom. The author analyzes the concept and discusses the role it plays in Kant's moral philosophy and psychology. He also considers in full detail the critical literature on the subject from Kant's own time to the present day. In the first part Professor Allison argues that at the center of the Critique of Pure Reason there is the foundation for a coherent general theory of rational agency. The second part employs this account of rational agency as a key to understanding Kant's concept of moral agency and associated moral psychology. The third part focuses on Kant's attempt to ground both moral law and freedom in the Groundwork and the Critique of Practical Reason. This is a major contribution to the interpretation of Kant which will be of special interest to scholars and graduate students of Kant's moral theory.